2011
DOI: 10.1101/gr.124644.111
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide depletion of replication initiation events in highly transcribed regions

Abstract: This report investigates the mechanisms by which mammalian cells coordinate DNA replication with transcription and chromatin assembly. In yeast, DNA replication initiates within nucleosome-free regions, but studies in mammalian cells have not revealed a similar relationship. Here, we have used genome-wide massively parallel sequencing to map replication initiation events, thereby creating a database of all replication initiation sites within nonrepetitive DNA in two human cell lines. Mining this database revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
211
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(233 citation statements)
references
References 53 publications
15
211
1
Order By: Relevance
“…But, in contrast to ORC-binding profiles in Drosophila (MacAlpine et al, 2010), gene bodies rather than promoter regions of active genes were enriched with initiation events (Cayrou et al, 2011). Furthermore, both studies found that initiation events were underrepresented at the actual transcription start sites (TSS) and that CpG-rich sequences were enriched with initiation events (Cayrou et al, 2011;Martin et al, 2011). …”
Section: Potential Origins Of Replication Are Subject To Developmentamentioning
confidence: 96%
See 1 more Smart Citation
“…But, in contrast to ORC-binding profiles in Drosophila (MacAlpine et al, 2010), gene bodies rather than promoter regions of active genes were enriched with initiation events (Cayrou et al, 2011). Furthermore, both studies found that initiation events were underrepresented at the actual transcription start sites (TSS) and that CpG-rich sequences were enriched with initiation events (Cayrou et al, 2011;Martin et al, 2011). …”
Section: Potential Origins Of Replication Are Subject To Developmentamentioning
confidence: 96%
“…More recently, two genome-scale studies have used nascentstrand analysis (see Box 2) to map replication origins in two human cancer cell lines, three mouse cell lines and a Drosophila cell line (Cayrou et al, 2011;Martin et al, 2011). In all lines, the majority of initiation events were associated with active transcription units.…”
Section: Potential Origins Of Replication Are Subject To Developmentamentioning
confidence: 99%
“…DNA combing technology, replication timing analysis, short nascent strand (SNS) enrichment, and bubble trapping approaches suggest that DNA replication initiation sites are enriched in CpG-rich regions, open chromatin domains, and transcriptional regulatory elements (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, these methods lack the necessary resolution to investigate important relationships of ORC binding with other features of the genome.…”
mentioning
confidence: 99%
“…In contrast, progress in elucidating the chromatin-mediated control of replication origin usage and efficiency as well as of the maintenance of the spatio-temporal replication program in higher eukaryotes has been rather slow (Berezney et al 2000;Bogan et al 2000;Gilbert 2001Gilbert , 2010Méchali 2001Méchali , 2010Bell & Dutta 2002;McNairn & Gilbert 2003;Aladjem 2007;Courbet et al 2008;Hamlin et al 2008). Only very recently nascent DNA strands synthesized at origins were purified by various methods to map replication origins genome-wide in mouse (Sequeira-Mendes et al 2009;Cayrou et al 2011) and human (Lucas et al 2007;Cadoret et al 2008;Karnani et al 2010;Martin et al 2011;Mesner et al 2011;Valenzuela et al 2011). The set of replication origins identified so far are strongly associated with annotated promoters and seem to be enriched in transcription factor binding sites (Cadoret et al 2008;Karnani et al 2010;Besnard et al 2012) and in CpG islands (Cadoret et al 2008;Sequeira-Mendes et al 2009;Cayrou et al 2011).…”
Section: Introductionmentioning
confidence: 99%